2017
DOI: 10.1016/j.pharep.2017.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants for irritable bowel syndrome—A systematic review

Abstract: Generally, antidepressants improved IBS symptoms. In comparison with placebo, tricyclic therapy for IBS was more effective than selective serotonin reuptake inhibitors. Antidepressants might be an alternative therapy for patients suffering from IBS, especially diarrhea-predominant IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Neuromodulatory analgesic agents, such as tricyclic antidepressants and selective serotonin reuptake inhibitors (SSRI), have an established role in the management of IBS; however, the number needed to treat remains relatively large . The exact mode of action remains unclear but may be due to the interference with specialised brain networks involving emotional and cognitive processing of pain or by engaging descending pathways to alter pain transmission at the level of the dorsal horn of the spinal cord, both mechanisms can in turn alter conditioned pain modulation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuromodulatory analgesic agents, such as tricyclic antidepressants and selective serotonin reuptake inhibitors (SSRI), have an established role in the management of IBS; however, the number needed to treat remains relatively large . The exact mode of action remains unclear but may be due to the interference with specialised brain networks involving emotional and cognitive processing of pain or by engaging descending pathways to alter pain transmission at the level of the dorsal horn of the spinal cord, both mechanisms can in turn alter conditioned pain modulation .…”
Section: Discussionmentioning
confidence: 99%
“…There was a clear correlation between baseline conditioned pain modulation and that after receiving Pregabalin (r = 0.73, P < 0.0001). Their findings indicate that the increase in conditioned pain modulation after Pregabalin was more pronounced in those individuals with a low baseline conditioned pain modulation while participants with initially high conditioned pain modulation may have reduction in conditioned pain modulation after receiving Pregabalin.Neuromodulatory analgesic agents, such as tricyclic antidepressants and selective serotonin reuptake inhibitors (SSRI), have an established role in the management of IBS; however, the number needed to treat remains relatively large [54][55][56][57]. The exact mode of action remains unclear but may be due to the interference with specialised brain networks involving emotional and cognitive processing of pain or by engaging descending pathways to alter pain transmission at the level of the dorsal horn of the spinal cord, both mechanisms can in turn alter conditioned pain modulation 58.…”
mentioning
confidence: 99%
“…Since stress‐related disorders include anxiety and depression, and the development of irritable bowel syndrome have mutual influences, several researches have reported that psychological stress or negative affective symptoms could precipitate or exacerbate IBS through this axis . The effects of antidepressants, anxiolytics, and even antipsychotics in the treatment of IBS also hint at the correlations between IBS and psychiatric disorders. The recent development of probiotics also found that gut flora could play a role in the development and management of IBS …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, patients with inflammatory bowel disease (IBD), irritable bowel syndrome (IBS), and depression have been found to have an altered intestinal microbiome . Furthermore, they have an increased risk of developing depression and anxiety disorder, and treatment with antidepressants can improve their bowel symptoms as well as their mood, reinforcing the connection between dysbiosis and mood …”
Section: Parallel Mechanisms Between Gut‐brain‐axis and Skin‐brain Axismentioning
confidence: 99%